Multiple organ tuberculomas in infant - Asriyani,Sri; Syahril,Erlin; Nelly (Journal of Clinical Imaging Science)
Tuberculoma is a space-occupying lesion resulting from the containment of the inflammatory process in metastatic tuberculosis, which most commonly occur in the brain and lungs. This form of tuberculosis is commonly found in adults, but rarely seen in children. Here we reported a case of an infant with multiple organ tuberculomas. The patient had unspecific signs and symptoms. There were also multiple cervical lymph nodes enlargement and weakness in both lower limbs and right hand. Chest radiograph showed a left pulmonary mass which was further evaluated by thorax CT imaging and revealed pulmonary tuberculoma, mediastinal lymphadenopathies, and pneumonia. Cervical ultrasound showed multiple cervical lymphadenites and brain MRI with contrast showed multiple intracranial tuberculomas with focal meningitis. A microscopic examination from gastric lavage sampling revealed a positive acid-fast bacillus smear and a biopsy of a lump in the neck demonstrated a picture of chronic granulomatous lymphadenitis that supports tuberculosis infection. Through this case, we emphasize the importance of the various appearance of pulmonary and extrapulmonary tuberculosis in infants.